Pooled analysis of the prognostic relevance of progesterone receptor status in five German cohort studies - Salmen, Jessica; Neugebauer, Julia; Fasching, Peter; Häberle, Lothar; Huober, Jens; Woeckel, Achim; Rauh, Claudia; Schuetz, Florian; Weissenbacher, Tobias; Kost, Bernd; Stickeler, Elmar; Klar, Maximilian; et al. (Breast Cancer Research and Treatment, 2014)
The progesterone receptor (PR) has been increasingly well described as an important mediator of the pathogenesis and progression of breast cancer. The aim of this study was to assess the role of PR status as a prognostic factor in addition to other well-established prognostic factors. Data from five independent German breast cancer centers were pooled. A total of 7,965 breast cancer patients were included for whom information about their PR status was known, as well as other patient and tumor characteristics commonly used as prognostic factors. Cox proportional hazards models were built to compare the predictive value of PR status in addition to age at diagnosis, tumor size, nodal status, grading, and estrogen receptor (ER) status. PR status significantly increased the accuracy of prognostic predictions with regard to overall survival, distant disease-free survival, and local recurrence-free survival. There were differences with regard to its prognostic value relative to subgroups such as nodal status, ER status, and grading. The prognostic value of PR status was greatest in patients with a positive nodal status, negative ER status, and low grading. The PR-status adds prognostic value in addition to ER status and should not be omitted from clinical routine testing. The significantly greater prognostic value in node-positive and high-grade tumors suggests a greater role in the progression of advanced and aggressive tumors.
EVALuna2:6666